The global effects of Asian haze [air pollution]. - Lelieveld, J.
The authors describe how a thick layer of aerosols just discovered above the Indian Ocean by an international team may be a far-reaching influence on climate systems. The layer of haze was the discovery of the Indian Ocean Experiment (Indoex), an international field experiment that has been collecting surface and atmospheric data over the tropical Indian Ocean since 1996
Keywords: Asian haze; Indian Ocean; Indian Ocean Experiment; Indoex; Aerosols; Air pollution; Climate systems; Global climate effects; International field experiment